Catalytic conversion of biomass-plastic blend to high-quality bio-oil via co-pyrolysis using chicken eggshell waste as deoxygenation catalyst: A feasibility study - Seah, Chiun Chao; Hafriz, R.S.R.M.; Tan, Ee Sann; Salmiaton, A.; Shamsuddin, A.H. (Materials today : proceedings, 2024)
Energy shortages and reliance on fossil fuels have led to the discovery of new technologies to reduce the environmental impact by taking advantage of excess plastic and turning them into usable alternative fuels using the pyrolysis method. However, the oil produced contains highly oxygenated compounds, which are considered a downside to the fuel characteristics, along with a low by-product yield. Therefore, feasibility study of calcined eggshells as a deoxygenation catalyst in the co-pyrolysis of empty fruit bunch (EFB)/high-density polyethene (HDPE) blend and compare it quantitatively and qualitatively with bio-oil produced using a commercial zeolite-based catalyst, ZSM-5 and Fluid Catalytic Cracking (FCC) at 500 °C operating temperature, 10 ft3/min N2 flow rate, 10 wt% catalyst loading, 1:1 HDPE:EFB ratio and 75 g feedstock with 60 min operating time in a stainless-steel fluidised bed reactor. Natural and calcined chicken eggshells were characterised using TGA/DTG, while the bio-oil produced was characterised using GC–MS. By using FCC catalyst, the highest oil yield (13.2 wt%) with high oxygenated compounds was obtained. The oil with the highest hydrocarbon yield (61.62 %) and lowest oxygenated compound content (38.38 %) was obtained using a calcined chicken eggshell (CES) catalyst. Calcined chicken eggshell (CES) catalysts showed better performance than commercial catalyst in terms of the quality and average yield of bio-oil produced. This study confirmed that the presence of a catalyst in the co-pyrolysis of EFB and HDPE can improve the yield of bio-oil and enhance its quality.